Bacillus coagulans prevents the decline in average daily feed intake in young piglets infected with enterotoxigenic Escherichia coli K88 by reducing intestinal injury and regulating the gut microbiota - Zhang, Yanyan; Tian, Xiaorong; Dong, Yi; Li, Rui; Shen, Meng; Yi, Dan; Wu, Tao; Wang, Lei; Zhao, Di; Hou, Yongqing (Frontiers in Cellular and Infection Microbiology, 2023)
Background Enterotoxigenic Escherichia coli (ETEC), an important intestinal pathogen, poses a significant threat to the intestinal health of piglets. Bacillus coagulans (BC), a potential feed additive, can improve the intestinal function of piglets. However, the effects of BC on growth performance and intestinal function in ETEC-infected piglets are still unclear. In this study, 24 7-day-old piglets were randomly assigned to three treatment groups: control group (fed a basal diet), ETEC group (fed a basal diet and challenged with ETEC K88) and BC+ETEC group (fed a basal diet, orally administered BC, challenged with ETEC K88). During Days 1-6 of the trial, piglets in the BC+ETEC group were orally administered BC (1×108CFU/kg). On Day 5 of the trial, piglets in the ETEC and BC+ETEC groups were orally administered ETEC K88 (5×109CFU/piglet). Blood, intestinal tissue, and content samples were collected from the piglets on Day 7 of the trial. Results The average daily feed intake in the ETEC group was significantly reduced compared to that of the control group. Further research revealed that ETEC infection significantly damaged the structure of the small intestine. Compared to the control group, the villus height and surface area of the jejunum, the ratio of villus height to crypt depth in the duodenum and jejunum, and the activities of catalase and total superoxide dismutase in the jejunum were significantly reduced. Additionally, the levels of myeloperoxidase in the jejunum, malondialdehyde in the plasma and jejunum, and intestinal epithelial apoptosis were significantly increased in the ETEC group. However, BC supplementation had significantly mitigated these negative effects in the BC+ETEC group by Day 7 of the trial. Moreover, BC supplementation improved the gut microbiota imbalance by reversing the decreased numbers of Enterococcus, Clostridium and Lactobacillus in jejunum and Escherichia coli, Bifidobacterium and Lactobacillus in the colon, as well as the increased number of Escherichia coli in the jejunum induced by ETEC K88. Conclusions Overall, BC supplementation reduced the decline in average daily feed intake in ETEC K88-infected piglets by attenuating intestinal epithelial apoptosis and oxidative stress and regulating the gut microbiota. This suggests that BC may be used to prevent intestinal infections caused by ETEC in piglets.